From space in modern art to a spatial art history reassessing constructivism through the publication "Circle" (1937) - Vinzent, Jutta 1968-2021 (SpatioTemporality / RaumZeitlichkeit, 2020)
This book traces artists’ theories of constructive space in the first half of the twentieth century. Drawing on these concepts and recent theories on space, it develops a methodology termed ‘Spatial Art History’ that conceives of artworks as physical spatio-temporal things, which produce the social, to overcome the reductive understanding of art as a mere mirror or facilitator of society